"It's not how it looks!" Exploring managerial perspectives on employee wellbeing. Issue 4 (August 2017) - Vakkayil, Jacob; Torre, Edoardo Della; Giangreco, Antonio
Abstract: The literature on employee wellbeing (EW) has largely focussed on employees' subjective experiences and has generally assumed that managers' interpretations of EW are consistent and non-problematic. Tensions inherent in managing complex expectations, and diverse results, have not been adequately investigated, and ways in which EW practices are viewed by senior managers have not been sufficiently examined. This paper attempts to fill this gap by exploring the perceptions of senior managers with human resources (HR) responsibilities affecting EW. There is a specific focus on the tensions experienced by these senior managers and the related tactics they adopted to successfully manage them. We gathered data from focus groups made up of 20 senior managers from companies operating in the Milan County in Italy. An analysis of this data identified four predominant dimensions of EW, as well as the tensions felt by the managers and the various tactics they used to overcome them. Finally, we classified the interpretative tactics into four broad resolution strategies (i.e. flexible, integrative, separated and reciprocal thinking ) that senior managers adopted to cognitively address their experience of tensions. Highlights: Explores the dynamics of senior managers' perceptions of employee wellbeing. Highlights internal tensions experienced as a result of multiple factors. Describes tactics used by senior managers to overcome tensions. Identifies four broad strategies that help in resolution and alignment.